2002
DOI: 10.2151/jmsj.80.205
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Efficiency in the Tropical Deep Convective Regime: A 2-D Cloud Resolving Modeling Study.

Abstract: Precipitation efficiency in the tropical deep convective regime is analyzed based on the hourly data from a 2-D cloud resolving simulation. The cloud resolving model is forced by the large-scale vertical velocity, zonal wind and large-scale horizontal advections derived from TOGA COARE for a 20-day period. Large-scale precipitation efficiency (LSPE) is defined as a ratio of surface rain rate to the sum of surface evaporation and moisture convergence, and cloud-microphysics precipitation efficiency (CMPE) is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 27 publications
3
45
1
Order By: Relevance
“…As defined, α is dependent on the cloud properties and types, entrainment rate, and relative humidity of the environment (Li et al 2002;Sui et al 2007). Differentiating Eq.…”
Section: Changing Rainfall Characteristicsmentioning
confidence: 99%
“…As defined, α is dependent on the cloud properties and types, entrainment rate, and relative humidity of the environment (Li et al 2002;Sui et al 2007). Differentiating Eq.…”
Section: Changing Rainfall Characteristicsmentioning
confidence: 99%
“…The 2D model setup has been used to successfully simulate tropical rainfall (Li et al 1999), severe tropical storm and typhoon (Wang et al 2009;Yue et al 2009), and pre-summer heavy rainfall . Similar experiment data of TOGA COARE have been analyzed to study surface rainfall processes (Gao et al 2005a), precipitation efficiency (Li et al 2002a, Sui et al 2005, cloud merging (Ping et al 2008), diurnal variation of rainfall (Gao and Li 2010a), and effects of ice cloud on rainfall (Gao et al 2006). …”
Section: Model Experiment and Rain Microphysical Budgetmentioning
confidence: 99%
“…Previous studies have shown that the large scale precipitation efficiency could exceed 100% in midlatitude mesoscale convection complexes, due to vigorous microphysical processes in the ice-phase processes in deep clouds. (Gamache and Houze 1983;Ferrier et al 1996;Li et al 2002).…”
Section: Regional Water Cyclementioning
confidence: 99%